2017
DOI: 10.1038/srep42226
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 axis induced miR-125b promotes invasion and confers 5-fluorouracil resistance through enhancing autophagy in colorectal cancer

Abstract: The activation of CXCL12/CXCR4 axis is associated with potential progression of cancer, such as invasion, metastasis and chemoresistance. However, the underlying mechanisms of CXCL12/CXCR4 axis and cancer progression have been poorly explored. We hypothesized that miRNAs might be critical downstream mediators of CXCL12/CXCR4 axis involved in cancer invasion and chemoresistance in CRC. In human CRC cells, we found that the activation of CXCL12/CXCR4 axis promoted epithelial-mesenchymal transition (EMT) and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 39 publications
0
98
2
Order By: Relevance
“…For example, miR-125b-5p inhibits breast cancer by targeting KIAA1522, [16] suppresses esophageal squamous cell carcinoma by regulating HMGA2, [26] enhances the chemotherapy sensitivity of gallbladder cancer by downregulating Bcl2, [33] and selectively targets IRF4 in multiple myeloma cells. [35] However, in this study, we did not notice the coexpression of miR-125b with CXCL12/CXCR4 axis in HCC. [35] However, in this study, we did not notice the coexpression of miR-125b with CXCL12/CXCR4 axis in HCC.…”
Section: Discussioncontrasting
confidence: 70%
“…For example, miR-125b-5p inhibits breast cancer by targeting KIAA1522, [16] suppresses esophageal squamous cell carcinoma by regulating HMGA2, [26] enhances the chemotherapy sensitivity of gallbladder cancer by downregulating Bcl2, [33] and selectively targets IRF4 in multiple myeloma cells. [35] However, in this study, we did not notice the coexpression of miR-125b with CXCL12/CXCR4 axis in HCC. [35] However, in this study, we did not notice the coexpression of miR-125b with CXCL12/CXCR4 axis in HCC.…”
Section: Discussioncontrasting
confidence: 70%
“…Autophagy may exert an inhibitory effect in early stage tumors, reducing invasion, and metastasis. During later stages, autophagy promotes metastasis by supporting cell survival following ECM detachment and preventing cell dormancy upon ECM reattachment . Autophagy is already known to play an important role in CRC progression .…”
Section: Introductionmentioning
confidence: 99%
“…Cellular ROS levels closely associated with the regulation of autophagy, which plays an important role in cancer metastasis by enhancing EMT . Thus, we next examined whether MSC coculture promotes autophagy activation in A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, a series of autophagy‐related (Atg) protein, such Beclin‐1 (mammalian homologue of Atg6) are elevated and contributed to the maturation of autophagosomes and formation of autolysosomes. Whereas some studies have shown that autophagy could inhibit cancer cell migration and invasion, particularly during the early stages of tumour initiation, as well as suppress EMT by degrading EMT‐associated transcription factors, other studies have shown that autophagy can enhance cancer metastasis via EMT . In colorectal cancer cells, enhancing autophagy is able to increase cell invasion, EMT, and chemotherapy resistance .…”
Section: Introductionmentioning
confidence: 99%